EFFECT OF RETENTION TIME OF PALM OIL MILL EFFLUENT ON GROWTH AND YIELD OF BABY CUCUMBER ON PEAT SOIL - Sarah Dhayan; Warganda warganda; Dini Anggorowati (Fakultas Pertanian Universitas Tanjungpura, 2019)
This study aims to find the best Palm Oil Mill Effluent (POME) retention time for baby cucumber’s growth and yield on peat soil. The study is conducted on Sungai Selamat Street, Siantan Hilir, East Pontianak District, Pontianak City. The study period began from February 16th, 2019 until May 11th, 2019. The design used in this study is a field experiment method with a Randomized Block Design pattern consisting of 6 treatments, namely: m0 (without incubation of POME), m1 (2 weeks incubation of POME), m2 (3 weeks incubation of POME), m3 (4 weeks incubation of POME), m4 (5 weeks incubation of POME), and m5 (6 weeks incubation of POME), each treatment is repeated 4 times and each plot consists of 3 observation sample plants and 1 destructive observation sample plant. The results showed that the retention time of POME on peat soil could increase yields on baby cucumber plants, especially on variable number of fruits yielded of each plant, fruit’s diameter, fruit’s weight each plant, and the weight of each fruit. The retention time of POME for 5-6 weeks can increase the number of fruits, fruit’s diameter, fruit’s weight each plant, and the weight of each fruit. Keywords: baby cucumber, retention time, peat soil, POME.